The Meaning of Happiness for Teenagers in Broken Home - Apriyanti, Kurnia; Maghfira Nisza, Nur; Fasrin, Firawati (Jurnal Multidisiplin Indonesia, 2024)
The aim of this research is to understand the meaning of happiness experienced by broken home teenagers and efforts to achieve happiness as broken home teenagers. The method in this research uses qualitative methods, with a phenomenological approach. Data collection techniques involve interviews and the use of recording devices. The number of subjects in this study were three teenagers with sample characteristics, namely experiencing a broken home. The questions asked in the interview process are unstructured and conducted in a pleasant atmosphere. Data analysis techniques are data reduction, data presentation, conclusions and verification. The results of the research show that the three respondents in this study, namely teenagers who experienced a broken home, showed the meaning of happiness by referring to the aspects put forward by Seligmen (2005), namely a pleasant life (Pleasant Life), a meaningful life (Meaningful Life), and involvement. self (Engaged Life). The three respondents gave meaning to life even though they came from broken home family backgrounds, they were able to find happiness in a unique way that involved positive experiences, meaning in life, and active involvement. These results provide insight for practitioners and families to help broken home teenagers understand and create their happiness.